The duck cytochrome oxidase I (COI) gene: Sequence and patterns analysis for potential barcoding tool - R. SUSANTI; RETNO SRI ISWARI; FIDIA FIBRIANA; INDRIAWATI INDRIAWATI (Society for Indonesian Biodiversity, 2018)
Susanti R, Iswari RS, Fibriana F, Indriawati. 2018. The duck cytochrome oxidase I (COI) gene: Sequence and patterns analysis for potential barcoding tool. Biodiversitas 19: 997-1003. The local duck DNA barcoding is still rarely conducted in Indonesia while DNA barcoding is extensively used as a tool of species identification and delineation tool. This study aimed to analyze the sequence and patterns of Central Javanese ducks mitochondrial cytochrome c oxidase subunit 1 (COI) gene. Feather samples of seven breeds of native duck were collected from traditional husbandries in Central Java. The samples were employed for DNA extraction and COI gene amplification. Five haplotypes were obtained from 35 samples, i.e., haplotype A, B, C, D, and E. Also, 9 variable sites with synonym substitution was detected in four nucleotides number 55, 61, 100, and 109; whereas five synonym substitutions were identified in the nucleotides number 36, 48, 51, 66, and 756. In conclusion, this study annotates that COI mtDNA gene is essential for local ducks barcoding system.